Determining priority criteria for using online learning media in Emergency Remote Teaching (ERT) using the Analytical Hierarchy Process (AHP) method - Permana, Hilman; Haritman, Erik (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2024)
Many institutions in Indonesia swiftly shifted their educational programs to online learning with minimal preparation due to the COVID-19 pandemic. This has resulted in a situation termed as Emergency Remote Teaching (ERT), defined as a temporary and abrupt shift from offline (face-to-face) to online (virtual) instructional delivery as a consequence of a disaster. It is crucial for educators to grasp key aspects of utilizing online learning media. This research aims to identify recommended criteria and alternatives for the use of online learning media from the educators’ perspective, employing the Analytical Hierarchy Process (AHP) method, which is suitable for ranking issues. This method involves a group decision-making process that employs comprehensive and multidimensional ranking in various domains. The research instrument comprises a questionnaire filled out by educators, including lecturers and teachers, totaling 13 respondents. The study reveals that the top-ranked criteria and alternative for the use of online learning media are the ease of operation criterion (K1) and the fastness alternative (A1). Future research is encouraged to further explore the application of the AHP method in other aspects of online learning